Comparative efficacy and safety of anti-cryptosporidial agents: an in vitro study on nitazoxanide, halofuginone lactate, KDU731, and paromomycin against Cryptosporidium parvum - Whitta, Saffron T. G.; Lamont, Bridget; Suwanarusk, Rossarin; Russell, Bruce M.; Muhsin-Sharafaldine, Morad-Rémy (Frontiers in Microbiology, 2024)
This study evaluates the in vitro effectiveness of the anti-cryptosporidial agents Nitazoxanide, Halofuginone, the pyrazolopyridine analogue KDU731, and Paromomycin in combating the significant zoonotic pathogen Cryptosporidium parvum. The study utilizes HCT-8 host cells to culture C. parvum and fluorescent microscopy / qPCR for detecting parasitic growth. The efficacy of the compounds was assessed by calculating their inhibitory concentrations against the total growth of C. parvum at 48 hours post-infection. The study further investigates the impact of these compounds on early parasitophorous vacuole formation, merozoite egress, host cell viability, and cell growth cycle. KDU731 displayed the most promising profile, with low nanomolar (102 nM ± 2.28) activity and negligible host cell toxicity. This study offers new insights into the relative efficacy and safety of various anti-cryptosporidial compounds, highlighting their stage-specific effects on C. parvum and the consequential impacts on host cells. Identifying safe and effective anti-cryptosporidial agents contributes significantly to the One Health approach, emphasizing the importance of integrated strategies in controlling zoonotic diseases.